(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The paper interprets performance and theoretical works of Maga Magazinović from the perspective of cultural studies, i.e., ideological criticism and feminist theories. It starts from the global context in which her modern dance was formed, and then it construes three narratives as interpretative frames. The first narrative deals with her work as an example of transnational idea of absolute dance. The second one deals with her work within the framework of cultural feminism and of construction of female choreographic and dance subject, as well as the imagined community of female performers and audience. The third narrative deals with physical culture and modern dance, and with its theoretical explications as discoursive techniques of performing national Yugoslav identity as singular as well as plural at the same time. This interpretation is based on contemporary world-system theories, in which the cultures are divided into core, semi-peripheral, and peripheral. As a result, the paper is focused on the way global cultural models are realized in local semi-peripheral system of Serbian and Yugoslav bourgeous culture.